Effects of fentanyl on isobaric ropivacaine in subarachnoid anaesthesia for lower abdominal and lower extremity surgeries - C.H., Murali; G., Laxmi Narsaiah (International Journal of Research in Medical Sciences, 2017)
Background:The addition of fentanyl to ropivacaine has shown to improve the quality of analgesia without compromising its benefits such as early mobilization and early voiding. This study evaluated the effects of adding fentanyl 25 mcg to isobaric ropivacaine 0.75% for spinal anaesthesia with regards to the onset of sensory block, maximum sensory level reached and the time to achieve it, time to two dermatome segment regression, onset of motor block, time for maximum motor blockade, duration of motor block, hemodynamic parameters and incidence of side effects. Methods: Hundred patients, male and female, ASA I or ASA II, aged 18 to 65 years scheduled for elective lower abdominal and lower extremity surgeries were randomized into two groups. Group R (control group) received 0.75% isobaric ropivacaine 22.5 mg (3 ml) and Group RF (study group) received 0.75% isobaric ropivacaine 22.5 mg (3 ml) and 25 mcg of fentanyl (0.5 ml). Intra operatively, sensory blockade was assessed by pin-prick method and motor parameters were assessed by modified Bromage scale at different time intervals. Haemodynamic parameters were monitored and side effects were also recorded Results: Both groups were comparable with respect to age, height, weight and duration of surgery. There was no significant difference in hemodynamics, onset of sensory and motor block, peak level of block, recovery from motor block, return of micturition and incidence of side effects with the addition of fentanyl to ropivacaine. There was a significant prolongation of the duration of sensory block (250.8±20.7 VS 362.1±15.1* min) and postoperative analgesia (320.56+15.32 VS462.41±38.42 *min) in Group RF (P < 0.001). Conclusions: It was concluded that the addition of 25 mcg fentanyl to 22.5mg of 0.75% isobaric ropivacaine for spinal anaesthesia significantly increases the duration of sensory block and decreases the rescue of analgesia with better hemodynamic stability, early recovery and mobilization.